The effect of sowing dates on the pod yield and some agronomic and quality characteristics of ‘Virginia’-type peanut variety ‘Halisbey’ in the Mediterranean environment - Halil Bakal; Bihter Onat; Halis Arioğlu; Leyla Güllüoğlu (Інтродукція Рослин, 2022)
The objective of this study was to determine the effect of different sowing dates on pod yield and some agronomic characteristics of the ‘Virginia’-type peanut cultivar ‘Halisbey’, and to determine the optimal sowing date in the Mediterranean region. This study was conducted in 2018 and 2019 at the Experimental Research Farm of Agricultural Faculty, Cukurova University in Adana, Turkey. The seeds were sown on seven dates: March 28, April 8, April 18, April 28, May 8, May 18 and May 28 each year. The experiment included a randomized complete block design with three replications. The plants were harvested 160 days after sowing, starting on September 8 every year. Pod number and pod weight per plant, 100 seeds weight, shelling percentage, oil and protein content, pod and kernel yield per hectare were investigated. As a result, pod number and weight per plant, 100 seeds weight, shelling percentage, pods and kernel yield values were found to be the highest at the experimental variant with May 8 sowing date. While the oil content decreased by delaying the sowing date, the protein content was increased. According to a two-year average, the highest pod yield (8136 kg ha-1) and kernel yield (5711 kg ha-1) were also obtained at the experimental variant with May 8 sowing date.